Building Performance Through Work Engagement and Social Emotional Learning: A Study on Non-ASN Employees of the Banten Ministry of Religion - Millatun Hanafiyah; Basrowi Basrowi; Khaeruman Khaeruman (Jurnal Masyarakat Maritim, 2025)
The purpose of this study was to determine the direct effect of work involvement and social emotional learning on work decision making. The direct effect of work involvement and social emotional learning on performance; Indirect effect of work involvement and social emotional learning on performance through work decision making. This study uses a quantitative method with a correlational approach. The population of this study were all honorary employees in the Regional Office and the Ministry of Religion Office in Banten Province, totaling 289 people. The sampling technique used was proportional random sampling. The sample size was 240 respondents. The research instrument was developed based on the grid compiled from the theory that has been explained on the theoretical basis. Data was collected using a questionnaire. The study was conducted in June-July 2024. The results of this study indicate that work involvement has a significant effect on work decision making. Social emotional learning has a significant effect on work decision making; Job involvement has a significant effect on Performance; Social emotional learning has a significant effect on performance; job involvement has a significant effect on performance through work decision making. Social emotional learning has a significant effect on performance through work decision making. The findings of this study, that work decision making is able to mediate the influence of work involvement and social emotional learning on performance through work decision making.